Household desalination ro system design and installation - Nguyen Van Hiep; Nguyen Trong Tuyen; Phan Manh Cuong (Journal of Technical Education Science, 2020)
In recent years, hydropower projects and exploitation of upstream MeKong river has been causing shortage of downstream. Moreover, the rising of sea level due to climate change in combination with low natural elevation of (the) Mekong Delta region made saltwater intrusion more serious. For instance, Ben Tre in Vietnam is one of the provinces suffering the most serious saltwater intrusion. According to reports in mid-March 2020, many rivers in the province have been affected by salinity of 7 - 10 ⁰/₀₀, living water sources reached the alarming level at 2⁰/₀₀, more (than) 8 times compared to 0.25⁰/₀₀ in the standard of drinking water quality QCVN 01:2009. In this situation, the authors have designed and implemented a semi-automatic household desalination system. It is applied RO technology for the ability of handling well feed water with the salinity within 0 - 2⁰/₀₀, ensuring water quality always meets the standard. The system also reaches a permeate flow of over 10 L/h, which helps to afford daily dietary needs of each person. In addition, the system operation and indicators of Total Dissolved Solids (TDS), salinity, filtered water volume can be remotely controlled and monitored by Android phone.